Neotropical páramos as biogeographic units - Diaz Acevedo, Carlos Javier (2020)
Introduction: Páramo has been defined from various points of view, which take into account different factors that are easy to recognize or measure, nevertheless at the biogeographic level it has been evaluated with criticized methods used to identify historical units. The analysis of endemicity, despite its importance and wide recognition, has not been used as a tool to evaluate Páramo. Objective: Determine whether the neotropical Páramo is one or several biogeographic units. Methods: We included distributional records from Aves, Amphibia, Mammalia, Reptilia, Marchantiophyta, and Spermatophyta. We found 7 025 species with 193 250 suitable occurrences obtained from the GBIF. We used each taxonomic group as an independent partition or as a component of a larger partition, such as total plants (Plants-T: Marchantiophyta + Spermatophyta), or total animals (Animals-T: Aves + Amphibia + Mammalia + Reptilia), or total evidence (Plants-T + Animals-T). In order to identify areas of endemism, we used the optimality criterion (NDM/VNDM) with grids of 0.5° or 0.25°. We calculated the intersection among polygons of previous Páramo definitions and the areas recovered in our analyses. Results: Both grid sizes, 0.25° and 0.5°, identified areas of endemism in different sectors along the Andean and Central American cordilleras, but only the 0.25° size allowed us to recognize areas/sectors with a higher resolution. We recovered eight areas, which were considered as subprovinces (Santa Marta-Perijá, Mérida, Santanderes-Boyacá, Cundinamarca, Central-Western Cordillera, Northern Ecuador, Central-South Ecuador, and Talamanca). These areas were between 4 and 66 % consistent with previous definitions. Conclusions: Páramo has been considered a single biogeographic unit, however, given our analyses we identified it as a unit composed of eight biogeographic subprovinces, which is consistent with some published studies.